(untitled) (Medical Forum Monthly, 2024)
Objective: To study the Emerging Down Syndrome Behavioral Phenotype from infancy to Early Childhood and to see Developmental Profile as a Predictor of this Behavior phenotype in Down Syndrome Children. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Development and Behavioral pediatrics, University of Child Health science, Children’s hospital Lahore and duration of study was 6 months from 1st January 2023 to 30th June 2023. Methods: It was a Cross-sectional study. Data was collected from Department of Development and Behavioral pediatrics, University of Child Health science, Children’s hospital Lahore and duration of study was 6 months. A sample of 42 Children having age 1-5 years was collected through purposive sampling technique. Results: In breakup of PEEP and SDQ tools, Cognition age of 9 (19%) patients was profound, 23 (48%) severe, 9 (19%) moderate and 7(15%) was mild delay. Socialization age of 4 (8%) patients was profound, 11 (23%) severe, 13 (27%) moderate, 11(23%) mild and 9 (19%) patients were age appropriate. Self-help age of 7(15%) patients was profound, 12 (25%) severe, 13 (27%) moderate, 10 (21%) was mild delayed and 6 (13%) patients were patients were age appropriate. Motor age of 8(17%) patients was profound, 13 (27%) severe, 15 (31%) moderate, 8 (17%) was mild delay and 4 (8%) patients were age appropriate. Expressive Llanguage age of 19 (40%) patients was profound, 22 (46%) severe,5 (10%) moderate 1(2%) was mild delay and 1 (2%) patients were age appropriate. Conclusion: Specific Behavioral Phenotype (BF) in children with Down Syndrome (DS) is consistent with relative strength in sociability, non-verbal abilities, receptive language, implicit memory skills and visuo spatial processing and relative weakness in gross & fine motor skills, verbal communication, visuo motor, cognitive functioning and motor planning.